Gunpowder, masculinity, and warfare in German texts, 1400-1700 - Brugh, Patrick (Changing perspectives on early modern Europe., 2019)
How gunpowder technology exploded heroes, heroics, and war stories from 1400 to 1700, and how German writers tried to glue them back together.